A Brief Discussion about Application of Artificial Intelligence in Computer Network Technology in the Era of Big Data. (November 2020) - Luo, Dongmei; Zhou, Corresponding author: Xiaodong
Abstract: With the rapid development of science and technology, the era of big data has come in full swing. A critical problem meriting reflection at present is how to take full advantage of this era in order to continuously improve the technological application level. As one of emerging technologies in modern society, artificial intelligence (AI) has achieved favorable effects when applied to different fields, e.g. AI computer network technology (CNT). The era of big data and AI were briefly expounded, the development of AI and its extensions in the era of big data were analyzed, and its application in CNT and development prospect were deeply explored, expecting to contribute to further application and development of AI in the era of big data.